2021
DOI: 10.1002/smll.202100554
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Performance Enhancement of Film by Pulse Electric Field and Multi‐Nanocomposite Strategy

Abstract: Thermoelectric (TE) film has wide potential application in low‐grade waste heat recovery and TE generation due to its quick response and multifunctional integration. Multi‐nanocomposite is a promising method to solve the difficulty of maintaining temperature difference and achieving a high figure of merit ZT. However, the depletion layer induced by the multi‐nanocomposite typically degrades performance. This study presents a simple and convenient method to solve this problem by pulse electric field (PEF). Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…[25] High power factor (PF) organic free-standing films with high electrical conductivity are still highly desired for making flexible OTEGs, especially for ntype materials. [23,24,[26][27][28][29] In this work, we reported that the PFs of MWCNT films could be further improved to 7.25 mW m −1 K −2 for p-type and 4.34 mW m −1 K −2 for n-type with high electrical conductivity over 10 000 S cm −1 through densifying the MWCNT films. The achieved PFs, to the best of our knowledge, are respectively the top values for both p-and n-type organic flexible TE films.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…[25] High power factor (PF) organic free-standing films with high electrical conductivity are still highly desired for making flexible OTEGs, especially for ntype materials. [23,24,[26][27][28][29] In this work, we reported that the PFs of MWCNT films could be further improved to 7.25 mW m −1 K −2 for p-type and 4.34 mW m −1 K −2 for n-type with high electrical conductivity over 10 000 S cm −1 through densifying the MWCNT films. The achieved PFs, to the best of our knowledge, are respectively the top values for both p-and n-type organic flexible TE films.…”
Section: Introductionmentioning
confidence: 79%
“…[ 25 ] High power factor (PF) organic free‐standing films with high electrical conductivity are still highly desired for making flexible OTEGs, especially for n‐type materials. [ 23,24,26–29 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that method C does not have a centrifugation process, higher D/G + and 2D/G + ratios can stem from short CNT fibers after the mortar agate process. However, the results of Raman spectra cannot explain the change in the thermoelectric performance of CNT yarns because it is known that the Seebeck coefficient decreases by increasing the carrier density, which is related to the increase of defect density. , Therefore, the defect density of CNTs is not the major contributor to the difference in thermoelectric performance with different dispersion methods.…”
Section: Resultsmentioning
confidence: 99%
“…There are the familiar characteristics such as no moving parts, no emissions, long operating lifetime, and low maintenance costs; Micro TEC also delivers quick-response and the high-precision tem-perature control by regulation of the input current, making it suitable for spot cooling. The small size and light weight make it the most preferred temperature control solution in electronic components and in other size-critical applications [7,8] .…”
mentioning
confidence: 99%